2021
DOI: 10.1007/s00210-021-02125-y
|View full text |Cite
|
Sign up to set email alerts
|

Comparison of the tissue distribution and metabolism of AN1284, a potent anti-inflammatory agent, after subcutaneous and oral administration in mice

Abstract: Purpose. To establish a liquid chromatography/mass spectrometry method to compare the tissue distribution and metabolism of AN1284 after subcutaneous and oral administration at doses causing maximal reductions in IL-6 in plasma and tissues of mice.Methods. Lipopolysaccharide activated RAW 264.7 macrophages were used to detect the antiin ammatory activity of AN1284 and its metabolites. Mice were given AN1284 by injection or gavage, 15 min before lipopolysaccharide. The reduction of IL-6 measured after 4h.Result… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
3
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

1
0

Authors

Journals

citations
Cited by 1 publication
(4 citation statements)
references
References 32 publications
(31 reference statements)
1
3
0
Order By: Relevance
“…Neither did they produce significant differences in hepatic concentrations, but those of the indole metabolite were higher after 5 mg/kg/day. Although not measured in the current study, the hepatic concentrations of AN1284 after administration of 1 mg/kg/day in the drinking water that significantly reduced fibrosis in the CCl 4 model were similar to those achieved by administration of 2.5 mg/kg/day by mps ( 25 ).…”
Section: Discussionsupporting
confidence: 62%
See 3 more Smart Citations
“…Neither did they produce significant differences in hepatic concentrations, but those of the indole metabolite were higher after 5 mg/kg/day. Although not measured in the current study, the hepatic concentrations of AN1284 after administration of 1 mg/kg/day in the drinking water that significantly reduced fibrosis in the CCl 4 model were similar to those achieved by administration of 2.5 mg/kg/day by mps ( 25 ).…”
Section: Discussionsupporting
confidence: 62%
“…While the current study was in progress, we completed an examination of the pharmacokinetics and metabolism of AN1284 in mice. Peak drug concentrations were similar in plasma and liver after s.c. injection, but nearly 50-fold higher in the liver when the compound was given orally ( 25 ). This suggested that oral administration should enable AN1284 to reduce hepatic damage.…”
Section: Methodsmentioning
confidence: 99%
See 2 more Smart Citations